Penerapan Model Cooperative Script dalam Pembelajaran PKn untuk Meningkatkan Hasil Belajar Siswa Pada Konsep Bangga Sebagai Anak Indonesia - Syafrudin, Ulwan; Darmawan, Darmawan; Ridwan, Ita Rustiati (Sekolah Tinggi Agama Islam Negeri (STAIN) Curup, 2018)
In PKn Learning in the concept of being proud as an Indonesian child there are many third grade students of SDIT Harapan Ummat Jakarta who get a less than optimal score. From the results of observations, the teacher uses a less varied learning method so that it does not support student activity and is less focused on the subject matter. Therefore, to improve the learning process, using the Cooperative Script model is expected to help students improve and improve their learning outcomes. The specific purpose of this study is to identify the steps and improve student learning outcomes through the Cooperative Script model in PKn learning. The type of this research used was Classroom Action Research using the Kemis and Teggart models conducted at SDIT Harapan Ummat with 35 students. The results of this study experienced a lot of improvement in activities and learning outcomes. from the results of observing the activities of students in the first cycle that is 57%, with enough categories and experiencing an increase in the second cycle to 84%, with the category Very good. While the average value of student learning outcomes in pre-cycle 36, cycle I 75.2, and cycle II increased to 92. From the results obtained concluded that learning using Cooperative Script learning models in Civics learning on the concept of pride has succeeded with increasing learning outcomes students. Recommendations to teachers as a reference for preparing lesson plans in improving professional skills in teaching Civics material for students in their classrooms, as well as broadening teacher insights and knowledge in applying Cooperative Script learning models.